Pulmonary Function Tests in the Evaluation of Early Lung Disease in Cystic Fibrosis - Walicka-Serzysko, Katarzyna; Postek, Magdalena; Borawska-Kowalczyk, Urszula; Milczewska, Justyna; Sands, Dorota (Journal of clinical medicine, 2023)
Background: Properly evaluating respiratory system dysfunction is essential in children with cystic fibrosis (CF). This prospective study aimed to assess the course of early lung disease based on multiple breath nitrogen washout (MBNW), impulse oscillometry (IOS), and conventional techniques, such as spirometry and body plethysmography. Methods: Over a 2 year recruitment period, subjects with CF aged 7–18 performed pulmonary function tests (PFTs). Moreover, the nutritional and microbiological status, frequency of pulmonary exacerbations (PExs), and patients’ health-related quality of life (HRQoL) were assessed. Results: The mean age of the children (n = 69) was 14.09 ± 3.26 years; F/M 37/32. Spirometry-based diagnoses of normal lung function (forced expiratory volume in 1 s, FEV1 ≥ 90%pred), mild (FEV1 70–89%pred) and moderate (FEV1 40–69%pred) lung diseases were established in 34 (49.3%), 25 (36.2%), and 10 (14.5%) patients, respectively. An elevated lung clearance index (LCI > 6.98) was observed in 85% of the subjects with normal FEV1. The presence of Pseudomonas aeruginosa infection (n = 16) and the number of PExs treated with IV antibiotics were associated with significantly worse PFT results. Conclusions: MBNW and IOS are more helpful tools than conventional techniques in assessing early lung disease in CF. LCI is a more useful parameter for detecting functional abnormalities than FEV1 in school-age children.